Young athletes' perceptions of coach behaviors and their implications on their well- and ill-being over time - González, L.; Garcia-Merita, M.; Castillo, I.; Balaguer, I. (The Journal of Strength and Conditioning Research, 2016)
Grounded on basic psychological needs theory the purpose of this study was twofold: (a) to test the mediational role of basic psychological needs (satisfaction and thwarting), and (b) to test the model invariance over 2 consecutive seasons. Three hundred sixty young male athletes completed a questionnaire package tapping the variables of interest at 4 time points during 2 consecutive seasons. Results of the path analyses revealed that in both seasons, changes in perceived coach autonomy supportive style positively predicted changes in needs satisfaction which, in turn, positively predicted changes in self-esteem; changes in perceived coach autonomy supportive and controlling style negatively and positively, respectively, predicted changes in needs thwarting which, in turn, positively predicted changes in burnout and negatively in self-esteem. Only in the first season, changes in needs satisfaction emerged as a negative predictor of changes in burnout. The mediational role of basic psychological needs and the invariance of the aforementioned relationships over the 2 seasons were supported. Results emphasize the importance of having coaches promoting autonomy supportive atmospheres and avoiding controlling styles to facilitate athletes' well-being and to prevent their ill-being.